2013
DOI: 10.1007/s00425-013-1977-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of GPC-1 genes in hexaploid wheat

Abstract: In wheat, monocarpic senescence is a tightly regulated process during which nitrogen (N) and micronutrients stored pre-anthesis are remobilized from vegetative tissues to the developing grains. Recently, a close connection between senescence and remobilization was shown through the map-based cloning of the GPC (Grain Protein Content) gene in wheat. GPC-B1 encodes a NAC transcription factor associated with earlier senescence and increased grain protein, iron and zinc content, and is deleted or non-functional in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
82
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 41 publications
9
82
1
2
Order By: Relevance
“…Nevertheless, hexaploid wheats have five other NAM genes, three paralogous (on chromosomes 2A, 2B and 2D) and two homoeologous (on chromosomes 6A and 6D) of which NAM-A1 (6A) has the same role as NAM-B1 [4,8]. Most studies on NAM wheat genes used mutants [4,8], near isogenic lines [9][10][11][12] or RNAi lines [3,4] and few studies have focused on the cultivated diversity [6,13]. This paper aims to characterize natural variants of NAM-A1 in hexaploid bread wheat and to hypothesize on the biological mechanisms explaining their effects.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, hexaploid wheats have five other NAM genes, three paralogous (on chromosomes 2A, 2B and 2D) and two homoeologous (on chromosomes 6A and 6D) of which NAM-A1 (6A) has the same role as NAM-B1 [4,8]. Most studies on NAM wheat genes used mutants [4,8], near isogenic lines [9][10][11][12] or RNAi lines [3,4] and few studies have focused on the cultivated diversity [6,13]. This paper aims to characterize natural variants of NAM-A1 in hexaploid bread wheat and to hypothesize on the biological mechanisms explaining their effects.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that NAM transcription factors act on a specific subset of genes at early stages after anthesis, well before visible symptoms of senescence are observed (Pearce et al, 2014). Our work indicates that, at comparatively early stages of development, no differences in chloroplast ultrastructure seem to exist between control and to SE.…”
Section: Discussionmentioning
confidence: 51%
“…Evidence obtained here, which includes conservation of chloroplast size, their apparent complexity, thylakoid membrane integrity and intact grana stacking, suggest that preservation of chloroplast ultrastructure is a key component of the stay-green phenotype generated by the down-regulation of TaNAM genes. The finding that the attributes mentioned above are not 16 affected in RNAi plants provides an structural base for the observation made by Avni et al (2014) and more recently by Borrill et al (2015) showing that the stay-green phenotype generated, respectively, by the lack of TaNAM-A1 and TaNAM-D1 or RNAi-down regulation of all TaNAM genes expression in T. aestivum is actually companied by maintenance of photosynthesis. Taken together these data provide support to the idea that lack, or diminished, TaNAM activity generates a functional stay-green phenotype, and that this is accompanied by preservation of full chloroplast structure.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations